Методологія реалізації експорту даних, візуалізації та формування 3D-моделі механізму у спеціалізованій розрахунковій системі - Влах, В. В. (НТУ "ХПІ", 2015)
В статті розглядаються методи, за допомогою яких утворюється візуалізація механізмів та виконується передача даних з спеціалізованого програмного забезпечення в середовище AutoCAD. Пропоноване програмне забезпечення створювалось в середовищі Embarcadero Rad Studio Delphi методами об’єктно-орієнтованого програмування. Це значної мірою дало змогу реалізувати експорт кінематичної схеми механізму та сформувати код програми мовою AutoLISP, яка описує тривимірну модель.

The article deals with the ways in which formed mechanisms visualization and data transmission is performed from specialized software environment in AutoCAD. Featured software was created in the Embarcadero Rad Studio Delphi with methods of object-oriented programming. It is largely made it possible to implement-export the kinematic scheme of mechanism and create program code AutoLISP language, describing the three-dimensional model. Functions of the program include the possibility to research mechanisms in other systems. Program provides export of data in office applications Word and Excel and in automated design system AutoCAD. Export data in Word and Excel enables you to receive standard documents and tabular data for detailed analysis mechanism. Also this program has possible to implement exporting the kinematic scheme of mechanism and create program code AutoLISP language, which describing the 3D-model.
Methodology of realization the exporting data, visualization and the formation of 3D-model of the mechanism in a specialized system of calculating
Keywords: об’єктно-орієнтоване програмування; AutoLISP; AutoCAD; 3D-модель; Delphi; object-oriented programming